2012
DOI: 10.1007/s00415-012-6509-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, utilization, and costs of antiepileptic drugs for epilepsy in Germany—a nationwide population-based study in children and adults

Abstract: Nationwide analyses of drug use can provide a prevalence estimate of the underlying disease and can help in understanding the characteristics of treatment. This study aimed for such analyses regarding the utilization of antiepileptic drugs (AED) for epilepsy in Germany. In 2009, all 4,115,705 AED prescriptions of all German patients with statutory health insurance (70,011,508 persons) were retrospectively analyzed. The IMS(®) LRx database served as data source, which accesses nationwide pharmacy data centers p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
74
4
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 40 publications
14
74
4
2
Order By: Relevance
“…In Norway, the most commonly used drugs were valproic acid and lamotrigine in children in 2004-2009 [9]. In Germany, the most preferred AED was valproic acid, followed by carbamazepine and lamotrigine [10]. A cohort study from UK family practice in 2008 showed that valproic acid was most commonly prescribed, followed by lamotrigine and levetiracetam in patients 0-14 years of age [11].…”
Section: Utilization Of Individual Aedsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Norway, the most commonly used drugs were valproic acid and lamotrigine in children in 2004-2009 [9]. In Germany, the most preferred AED was valproic acid, followed by carbamazepine and lamotrigine [10]. A cohort study from UK family practice in 2008 showed that valproic acid was most commonly prescribed, followed by lamotrigine and levetiracetam in patients 0-14 years of age [11].…”
Section: Utilization Of Individual Aedsmentioning
confidence: 99%
“…These results conflicted with those from previous reports in which the use of newer AEDs increased but older AEDs remained the mainstay of treatment in children. In Germany, older AEDs were used in 70.4 % of patients, while 48.3 % received new AEDs in 2009 [10]. The use of new AEDs in epilepsy increased from 40 % in 2004 to 49 % in 2009 in Norway [9].…”
Section: Older Versus Newer Aedsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of epilepsy is estimated at 0.91%, and antiepileptic drugs were used by 634,566 patients in Germany in 2009 according to [28]. Since most epilepsy patients are in ambulant treatment, antiepileptic drugs can be detected in most, if not all, WWTP effluents, though data do not exist for all antiepileptic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Кроме то-го, следует отметить, что практически все исследователи в рамках тестирования новых стандартов изучали ламо-триджин. С нашей точки зрения, изучения в этом отноше-нии требуют и другие ПЭП, прежде всего вальпроат, оста-ющийся одним из самых широко применяемых препара-тов этой группы в мире [56][57][58][59]. В ожидании же результа-тов новых исследований при необходимости генерических замен ПЭП можно только рекомендовать использование ЛС с хорошо изученными свойствами (в том числе и фар-макокинетическими) в пределах одной и той же лекарст-венной формы.…”
unclassified